Childhood - Teguh Pratama (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This artwork is a musical expression that evokes a childlike atmosphere, depicting the innocence, joy, and imagination of childhood that is often forgotten over time. The creation of this work begins with two popular Indonesian children’s songs, which serve as the main source of inspiration for the piece titled Childhood. These two songs were then developed and rearranged with a creative approach, resulting in a new form that retains the basic character of the children's songs but is packaged in a more modern and artistic musical atmosphere. This work uses two main musical patterns: the Waltz, which emphasizes softness, harmony, and romance, and the Swing, which brings energy, dynamics, and the cheerfulness typical of children's music. The fusion of these two patterns is done by considering elements such as tempo, harmony, rhythm, and dynamics to create a communicative and expressive work. Through Childhood, it is hoped that this piece will serve as a reflection of childhood memories, a nostalgic medium for the listeners, and an effort to preserve and revitalize Indonesian children's songs so that they remain relevant and loved across generations.